Advanced SS: A Superscalar Simulator with Support for Operating System - Cruz, Eduardo H. M.; Gonçalves, Ronaldo A. L. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2010: Anais do XI Simpósio em Sistemas Computacionais de Alto Desempenho, 2010)
Computer simulation has allowed the analysis of behavior and performance of systems still in its design phase. The Advanced Superscalar Simulator project is a tool for simulation of a complete computer system, involving the simulation of a superscalar processor and an input and output system, with infrastructure for symmetric multiprocessing. It can also run an operating system in the simulated hardware, making the environment more close to reality. The processor simulator is designed so that it can run multiple instruction sets, and it currently supports x86-64. The input and output system contains hypothetical devices of keyboard, video, hard drive and timer interrupt controller. An operating system was designed to manage the simulated hardware. It provides control of interruptions, multiprogramming, virtual memory and a subset of the Linux system calls, therefore, being partially compatible with binaries generated for Linux. The simulator was validated through experiments with the Spec 2000 Benchmark and proved its applicability as a tool for performance analysis.